Sharing Channel Strategy With Customers’ Collaborative Consumption Behaviors - Dong, Shaozeng; Luan, Mingqiao; Chen, Lingming; Ali, Zulqurnain (Frontiers in Psychology, 2022)
Associated with the sharing economy, collaborative consumption behaviors often take place among customers. Different from the traditional consumption that customers purchase the product and own it, in the sharing economy, customers can access the product only for a particular period and the ownership of the product also belongs to the firm. In this paper, we develop a theoretical analysis model, and investigate the intrinsic connection between collaborative consumption and the sharing channel strategy. Adopting the sharing channel strategy, the firm has a chance to expand the market demand and improve its profit. In addition, we examine the impacts of other influential factors on a firm’s decisions, such as the unit product cost, surplus-value, and service capability coefficient.